2023
DOI: 10.21037/tlcr-22-613
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of immune checkpoint inhibitors in advanced non-small cell lung cancer harboring BRAF mutations

Abstract: Background: Despite immune checkpoint inhibitors (ICI) being widely used to treat patients with advanced non-small cell lung cancer (NSCLC), few studies examine the role of ICI in patients with protooncogene B-Raf, serine/threonine kinase (BRAF) mutations.Methods: A retrospective study was conducted for patients with BRAF-mutant NSCLC who received treatment at Shanghai Pulmonary Hospital between 2014 and 2022. Primary end point was progression-free survival (PFS). Secondary end point was best response (RECIST,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In a phase 3 trial of treatment-naive patients with metastatic non-squamous NSCLC, the combination of pembrolizumab, pemetrexed, and a platinum resulted in significantly longer median PFS compared with chemotherapy alone (8.8 versus 4.9 months; HR = 0.52; P < 0.001) 81 . In a small retrospective study in China, immunotherapy plus chemotherapy ( n = 9) in treatment-naive patients with BRAF V600E -mutant advanced NSCLC resulted in a significantly longer median PFS compared with chemotherapy or targeted therapy ( n = 20; 18.5 versus 4.1 months; P = 0.0098) 82 . This efficacy benefit with immunochemotherapy was not observed in later lines.…”
Section: Treatment Landscapementioning
confidence: 97%
See 1 more Smart Citation
“…In a phase 3 trial of treatment-naive patients with metastatic non-squamous NSCLC, the combination of pembrolizumab, pemetrexed, and a platinum resulted in significantly longer median PFS compared with chemotherapy alone (8.8 versus 4.9 months; HR = 0.52; P < 0.001) 81 . In a small retrospective study in China, immunotherapy plus chemotherapy ( n = 9) in treatment-naive patients with BRAF V600E -mutant advanced NSCLC resulted in a significantly longer median PFS compared with chemotherapy or targeted therapy ( n = 20; 18.5 versus 4.1 months; P = 0.0098) 82 . This efficacy benefit with immunochemotherapy was not observed in later lines.…”
Section: Treatment Landscapementioning
confidence: 97%
“…Median PFS was longer in the first line than in subsequent treatment lines in patients with WT (12.8 versus 5.6 months) and BRAF-mutant (11.2 versus 4.0 months) NSCLC. These studies suggest that immunotherapy-based treatments are an option for patients with BRAF V600E -mutant advanced NSCLC 82 , 83 .…”
Section: Treatment Landscapementioning
confidence: 97%
“…A similar combination of drugs was used to treat patients with advanced BRAF-mutant non-small cell lung cancer. Relapse-free survival in patients receiving a combination of an immune checkpoint inhibitor and targeted therapy was better than in those receiving targeted therapy alone (18.5 vs. 4.1 months, respectively) (Wang et al, 2023).…”
Section: Combining Immune Checkpoint Inhibitors With Targeted Therapymentioning
confidence: 94%
“…In contrast, Gibson et al observed higher PD-L1 expression in V600E (60% of cases) than in non-V600E (39% of cases), but again with no statistical significance (p = 0.27) [39]. Independently from PD-L1 expression, recent reports have underlined the important use of immune checkpoint inhibitors in BRAF-mutated NCSLCs, with a limited distinction between V600E and non-V600E [40].…”
mentioning
confidence: 92%